Electroencephalography (EEG) in the Study of Equivalence Class Formation. An Explorative Study - Arntzen, Erik; Steingrimsdottir, Hanna S. (Frontiers in Human Neuroscience, 2017)
Teaching arbitrary conditional discriminations and testing for derived relations may be essential for understanding changes in cognitive skills. Such conditional discrimination procedures are often used in what is termed stimulus equivalence research. For example, the participant is taught “if A then B” and “if B then C” relations to be tested whether emergent relations occur (“if B then A”, “if C then B”, “if A then C,” and “if C then A”). The purpose of the current explorative experiment was to study stimulus equivalence class formation in older adults with electroencephalography (EEG) as an additional measure. The EEG was used to learn about whether there was an indication of cognitive changes such as those observed in NCD. The present study included four participants who did conditional discrimination training and testing, preceded and ended with pre‐and post‐sorting of the stimuli used during training. EEG recordings were conducted before training, after training, before testing, and after testing. The results showed that two participants formed equivalence classes, one participant failed in one of the three test relations, and one participant failed in two of the three test relations. This fourth participant also failed to sort the stimuli in the accordance with the experimenter‐defined stimulus equivalence classes during post‐sorting. The EEG indicated no cognitive decline in the first three participants but possible mild cognitive impairment (MCI) in the fourth participant. The results suggest that equivalence class formation may provide information about cognitive changes impairments such as those that are likely to occur in the early stages of neurocognitive disorders (NCD). We suggest that the equivalence paradigm seems to an effective for diagnosing cognitive impairments The study recommends replication with a broader sample. Keywords: Electroencephalography, matching-to-sample, neurocognitive disorders, stimulus equivalence, older adults